Impurity Free Vacancy Disordering (IFVD) of InxGa1-xAs/InP Quantum Well Structures for Monolithic Integration of Different Optoelectronic Devices - P L Gareso (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2010)
Impurity free vacancy disordering (IFVD) technique has been used to study the atomic intermixing of InxGa1-xAs/InP quantum well structures using a SiO2 and a TiO2 dielectric layer. Three different indium composition in InGaAs QWs were investigated, lattice-matched (LM), compressively-strained (CS) and tensile-strained (TS). Based on Photoluminescence results, the atomic intermixing between the quantum well and the barrier regions enhanced when the samples were coated with SiO2 layers. Although TiO2 layers were able to suppress the intermixing in InGaAs/InP system, the suppression was not significant compared to the AlGaAs/GaAs system. Based on a fitting procedure that was deconvoluted from the photoluminescence spectra including theoretical modeling, the electron-heavy hole and electron-light hole transitions were identified and a ratio of the group V to the group III diffusion coefficients (k) were obtained. The k ratio of the InGaAs/InP samples capped with SiO2 is relatively larger than of samples capped with TiO2 layers.